2016
DOI: 10.1016/j.heares.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Model predictions for bone conduction perception in the human

Abstract: Five different pathways are often suggested as important for bone conducted (BC) sound: (1) sound pressure in the ear canal, (2) inertia of the middle ear ossicles, (3) inertia of the inner ear fluid, (4) compression of the inner ear space, and (5) pressure transmission from the skull interior. The relative importance of these pathways was investigated with an acousticimpedance model of the inner ear. The model incorporated data of BC generated ear canal sound pressure, middle ear ossicle motion, cochlear prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 53 publications
(93 reference statements)
2
52
0
Order By: Relevance
“…Experimental results in humans by Sohmer et al (2000) also reported that BC sound power from a vibration transducer applied directly to the dura caused sound perception which was attributed to sound transmission through the CSF. Moreover, experiments in human cadaver heads have shown that there is a sound pressure inside the skull during BC stimulation (Roosli et al 2016;Sim et al 2016), but it was estimated not to be important for BC hearing in the human with a normal functioning ear (Stenfelt 2016). However, it is not clear how the BC sound in the skull bone and skull interior interacts.…”
Section: Transmission Through the Skull Interiormentioning
confidence: 99%
“…Experimental results in humans by Sohmer et al (2000) also reported that BC sound power from a vibration transducer applied directly to the dura caused sound perception which was attributed to sound transmission through the CSF. Moreover, experiments in human cadaver heads have shown that there is a sound pressure inside the skull during BC stimulation (Roosli et al 2016;Sim et al 2016), but it was estimated not to be important for BC hearing in the human with a normal functioning ear (Stenfelt 2016). However, it is not clear how the BC sound in the skull bone and skull interior interacts.…”
Section: Transmission Through the Skull Interiormentioning
confidence: 99%
“…It is still impossible to predict the effect of stimulation at a set amplification, frequency, and site, so any simulations or theoretical modeling prove to be imprecise. This is due to an unusual complexity of phenomena occurring during the process of sound transmission via BC to the organ of Corti in the inner ear [Freeman et al, 2000;Stenfelt, 2006Stenfelt, , 2016Stenfelt and Goode, 2005a;Tonndorf, 1966;vonBékésy, 1960;Yoshida and Uemura, 1991], already mentioned in the Introduction.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results should be interpreted cautiously, as they need to be viewed as experimental. It is impossible to obtain the effect of mechanical wave transmission to the inner ear using all 5 physiological ways of BC (mentioned in the Introduction) in cadaver studies [Stenfelt, 2016;Stenfelt and Goode, 2005b]. In our study, a simulation of BC conditions was performed with the device anchored in the bone in a conventional site and 2 experimental sites.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the skull is segmented and separated by sutures, and has complex resonance features (Håkansson et al, 1994). Various attempts have been made to model and measure the properties of vibration transmission through the head, primarily in humans, and primarily aimed at understanding BCV hearing (Stenfelt, 2015, 2016). For the human head at least, the skull approximately moves as a rigid structure for BCV below 400 Hz (Stenfelt and Goode, 2005), as a resonant structure between 400 Hz to 2 kHz (Håkansson et al, 1994), and as a wave-propagating structure above 2 kHz (Stenfelt, 2015).…”
Section: The Vm and Vsepmentioning
confidence: 99%
“…That is, BCV stimuli can induce neural responses from all vestibular end-organs, despite primarily activating otolithic irregular afferent neurons (Curthoys et al, 2006). Whilst researchers have attempted to use the direction of the applied BCV to activate selected vestibular HCs, it is unlikely that this circumvents the complex 3-dimensional vibration of the inner ear and the complex transduction pathways (Stenfelt, 2015, 2016; Chhan et al, 2016). Mechanical engineers are well aware of the complexity of interpreting the vibrational response of a structure via its “impulse response”.…”
Section: The Vm and Vsepmentioning
confidence: 99%